Unveiling the support of 3D representation in mobile devices for pedestrians navigation aid - Abubakar, Adamu; Waili, T.; Mantoro, Teddy (2012)
The problem of getting lost anywhere by pedestrians that uses mobile device will be reduce when 3D representation (Map) of an environment is provided in his/her mobile devices. Over the years, there are growing number of pedestrian navigation aided application for mobile devices, Unfortunately certain issue concerning the use of mobile devices as a navigation aid, in regards to the pedestrian behavior while-on-the-go in a different environment under different condition were still not properly address. Moreover, we don't know whether it safe or not interacting with mobile device while walking around and some other related support. This paper consider pedestrian behavior under different conditions in different environment while on the go and proposed the design of an application in Android platform with 3D representation meant for mobile device as a pedestrian navigation aid and investigates user's satisfactions with the applications interface design quality. The result shows that pedestrians consider interacting with the application as safe while using it in a calm condition in an unknown location and also its best usage is for mostly when it provides an exploration of environment rather route only.